Impact of postoperative radiotherapy on survival and loco-regional control in node-negative oral cavity tumours classified as T3 using the AJCC Cancer Staging Manual eighth edition. Issue 2 (February 2019) - Subramaniam, N.; Balasubramanian, D.; Murthy, S.; Rathod, P.; Vidhyadharan, S.; Thankappan, K.; Iyer, S.
Abstract: According to the eighth edition of the AJCC Cancer Staging Manual (AJCC8), a depth of invasion (DOI) >10 mm is classified as pT3, representing a locally advanced tumour requiring postoperative radiotherapy (PORT). When node-negative, however, evidence regarding whether PORT improves loco-regional control or survival is unclear. To clarify this, two cohorts of patients were studied: (1) patients classified as pT3N0 by the seventh edition of the AJCC manual (AJCC7), with DOI >10 mm and a tumour diameter >4 cm (17 patients who received PORT), and (2) patients classified as pT1N0 and pT2N0 by AJCC7, with DOI >10 mm and a tumour diameter <4 cm (55 patients who did not receive PORT). Loco-regional control and survival were analysed. PORT was found not to impact overall survival or disease-free survival. It was also found not to impact local, regional, or distant recurrence. Although the two subsets of patients considered here (DOI >10 mm with tumour diameter below or above 4 cm) were previously distinct, they are both considered pT3 in AJCC8. Data from this study indicate that the routine administration of PORT to patients with a DOI >10 mm may not be warranted in the absence of other risk features such as nodal disease or close margins.